2001
DOI: 10.1210/jc.86.10.5017
|View full text |Cite
|
Sign up to set email alerts
|

PPAR /RXR  Heterodimers Control Human Trophoblast Invasion

Abstract: The ligand-dependent nuclear receptors PPARgamma and RXRalpha/beta were recently determined to be essential for murine placental development and trophoblast differentiation. In the current study we examined the expression and role of the PPARgamma/RXRalpha heterodimers in human invasive trophoblasts. We first report that in human first trimester placenta, PPARgamma and RXRalpha are highly expressed in cytotrophoblasts at the feto-maternal interface, especially in the extravillous cytotrophoblasts involved in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 0 publications
4
54
0
Order By: Relevance
“…Tarrade et al [95] reported that PPARg is highly expressed in human cytotrophoblasts at the feto-maternal interface, particularly in the extravillous cytotrophoblasts involved in uterus invasion. They also showed that both synthetic and natural PPARg agonists inhibited extravillous cytotrophoblast invasion and the treatment with PPARg antagonist facilitated the invasion process [95]. Recently, the analysis of PPARg-target genes in human trophoblast led to characterization of new factors engaged in the regulation of trophoblast invasion [82,83,96].…”
Section: Ppars In the Placentamentioning
confidence: 99%
“…Tarrade et al [95] reported that PPARg is highly expressed in human cytotrophoblasts at the feto-maternal interface, particularly in the extravillous cytotrophoblasts involved in uterus invasion. They also showed that both synthetic and natural PPARg agonists inhibited extravillous cytotrophoblast invasion and the treatment with PPARg antagonist facilitated the invasion process [95]. Recently, the analysis of PPARg-target genes in human trophoblast led to characterization of new factors engaged in the regulation of trophoblast invasion [82,83,96].…”
Section: Ppars In the Placentamentioning
confidence: 99%
“…Peroxisome proliferator-activated receptors (PPARs) have been implicated in several aspects of early pregnancy development including implantation, placentation, and trophoblast differentiation (Barak et al 1999, Lim & Dey 2000, Tarrade et al 2001. We and others have presented data implicating PPARs in the inflammatory events that contribute to normal labor at term (Lim & Dey 2000, Lappas et al 2002b, Berry et al 2003, Dunn-Albanese et al 2004, Ackerman et al 2005, Lindstrom & Bennett 2005, Froment et al 2006, Schaiff et al 2006, Fournier et al 2007, Holdsworth-Carson et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…PPAR-associated inflammatory mediator suppression suggests that a breakdown in PPAR expression or activity may be apparent during periods of preterm intra-amniotic infection, as seen in non-gestational tissue infections (Kielian et al 2008, Perez et al 2008. While some groups have investigated PPAR expression in first (Tarrade et al 2001, Capparuccia et al 2002, Rodie et al 2005 and second trimester placenta (Waite et al 2000, Rodie et al 2005 and serum samples throughout the course of pregnancy (Wieser et al 2008), data are lacking regarding the expression and activity of PPAR isoforms in association with preterm delivery, with and without infection. The aim of this study was to compare the expression and DNA binding activity patterns of PPAR isoforms and the expression of RXRA in human gestational tissues from term and preterm vaginal deliveries, and to determine the effect of infectionassociated preterm delivery on PPAR isoforms and RXRA expression.…”
Section: Introductionmentioning
confidence: 99%
“…During our study, the three bands observed for RXRA disappeared when the primary antibody was incubated in the presence of its own blocking peptide (data not shown) suggesting that the bands could represent different isoforms from the same protein that are present specifically in rat endometrium. To investigate changes in the expression of RXRA protein during initiation of decidualization, we quantified only the 54 kDa band for RXRA for several reasons; this is the band reported by the supplier; it is the only isoform found it in the human placenta ( Tarrade et al 2001); according to the literature, it is the only full-length 540 C Gillio-Meina and others form; and is the most abundant form of the protein that is present in most tissues and cell lines studied (Matsushima-Nishiwaki et al 1996, Dufour & Kim 1999, Zhong et al 2003. RXRA protein levels significantly increased (P!0.05) at 16 h and remained high at 32 h as compared with 0 and 2 h (Fig.…”
Section: Resultsmentioning
confidence: 99%